2018
DOI: 10.24189/ncr.2018.040
|View full text |Cite
|
Sign up to set email alerts
|

The wild reindeer (Rangifer tarandus: Cervidae, Mammalia) on the arctic islands of Russia: a review

Abstract: The article presents summary data on the wild reindeer's (Rangifer tarandus) distribution on islands in the Russian Arctic. It discusses the abundance, diet, and general state of knowledge about the species in remote areas, especially on Novaya Zemlya and Wrangel Island. Brief data are provided about domestic reindeer grazing on the Arctic islands. Literature data are complemented with research findings in recent years. A negative trend is demonstrated in the wild reindeer abundance; also the need for studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The main cause for Protected Areas establishment is a need to protect threatened and rare plants and animals from extinction. However, in most cases, conservation measures are focused on the largest and most remarkable animals (Shi et al 2008, Zhang et al 2015, Mizin et al 2018, Samson & Ramakrishnan 2018 and plants (Bauer et al 2016, Wicaksono et al 2016. Although conservation of these species is undoubtedly important, we should not ignore a need to study and preserve all imperiled organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause for Protected Areas establishment is a need to protect threatened and rare plants and animals from extinction. However, in most cases, conservation measures are focused on the largest and most remarkable animals (Shi et al 2008, Zhang et al 2015, Mizin et al 2018, Samson & Ramakrishnan 2018 and plants (Bauer et al 2016, Wicaksono et al 2016. Although conservation of these species is undoubtedly important, we should not ignore a need to study and preserve all imperiled organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Caribou and muskoxen are sparse or absent on many of the Canadian islands lacking wolverines (Ellef Ringnes, King Christen, Cornwall, Meighen, and Lougheed Islands; Jenkins et al 2011 ). Reindeer are similarly unreported on most islands of the Russian High Arctic that lack wolverines, particularly Franz Joseph Land and Severnaya Zemlya (Mizin et al 2018 ), whereas muskoxen are absent from all except Wrangel Island, where they were introduced in 1975 followed by the colonization of wolverines in subsequent decades (Starova et al 2014 ; Cuyler et al 2020 ). Conversely, caribou are present on all islands throughout the Arctic where wolverines are reported, although in regions with lower caribou densities muskoxen comprise a higher portion of the wolverine’s diet (Awan and Szor 2012 ).…”
Section: Distributionmentioning
confidence: 99%
“…In Norway, wild mountain reindeer (Rangifer tarandus tarandus) are now located in more than 20 virtually isolated sub-populations due to industrial development mainly occurring along valley bottom lands, leading to the loss, fragmentation and degradation of mountain reindeer habitat (Panzacchi et al, 2015). Several forest and tundra reindeer populations in the European part of northern Russia are regarded as vulnerable or near threatened (Vors and Boyce, 2009;Mizin et al, 2018). Furthermore, the status of Rangifer populations in Novaya Zemlya (Mizin et al, 2018), Finland (Antti Paasivaara, personal communication, https://www.suomenpeura.fi/en/wild-forest-reindeer/conservation-status.html; Danilov et al, 2018) and Canada (Gunn, 2016;COSEWIC, 2017) is considered uncertain, near threatened and endangered, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several forest and tundra reindeer populations in the European part of northern Russia are regarded as vulnerable or near threatened (Vors and Boyce, 2009;Mizin et al, 2018). Furthermore, the status of Rangifer populations in Novaya Zemlya (Mizin et al, 2018), Finland (Antti Paasivaara, personal communication, https://www.suomenpeura.fi/en/wild-forest-reindeer/conservation-status.html; Danilov et al, 2018) and Canada (Gunn, 2016;COSEWIC, 2017) is considered uncertain, near threatened and endangered, respectively. Furthermore, the effects of climate change in the Arctic, such as extreme warm spells and rain-on-snow events, are becoming more frequent (Hansen et al, 2014), and there have been marked decreases in populations, as reported for Rangifer tarandus subspecies (Kohler and Aanes, 2004;Forbes et al, 2016;Langlois et al, 2017).…”
Section: Introductionmentioning
confidence: 99%